Solar Panel Based Field Lighting at Madinathul Ilmi School in Muara Gembong District - Sunawar, Aris; Nursyahied, Imam; Naura, Naura; Y, Nur Hanifah (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Field lighting in schools is one of the important elements that support educational activities, especially at night. This study aims to evaluate the implementation of a solar panel-based lighting system at Madinathul Ilmi School located in Muara Gembong District. By utilizing renewable energy sources, namely solar energy, this system is designed to overcome the problem of limited access to electricity in remote areas and reduce dependence on fossil energy sources. The research methodology includes the planning, installation, and performance evaluation stages of the lighting system used. Analysis was carried out on energy efficiency, operational costs, and the resulting environmental impacts. The results of the study indicate that the solar panel-based lighting system is able to provide adequate lighting with lower operational costs compared to conventional systems. In addition, the use of solar panels also contributes positively to reducing carbon emission.